Життя, присвячене людям - Smilyanets, N.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The article illustrates stages of life and scientific achievements of a breeder Vasiliy Petrovich Grin, his contribution to agricultural science.